Federalismo e as possíveis alterações no território dos estados federados - Balera, Felipe Penteado (2012)
Federation is one form of state that countries may adopt. In those countries with large territory this is the system that better conforms with the legal Democratic State, considering that the existence of political spheres of government capable to manage and regulate on portions of the country s territory could approach citizens to government and allow people to more easily claim their rights and interests. Not for any other reason, among the eight largest countries in the world by land area (Russia, Canada, China, United States, Brazil, Australia, India and Argentina), seven explicitly adopt federalism in their constitutions. The only one that does not expressly adopts federalism, that is China, has, even if incipiently, certain distribution of powers to local authorities. However, federalism does not consist in an absolute rule applied in the same way in those countries that adopt it. Each federation has a different way of political organization, taking into account the core characteristics and the historic formation of the country. Thus, countries formed by multiples nationalities that speak distinctive languages, such as Russia and India, must take care about the peaceful coexistence among different ethnic groups. On the other hand, the same care is unnecessary in countries comprises a sole nation even if, in origin, such nation has miscegenation from colonists, natives and immigrants with almost everyone speaking the same language, such as Brazil, Australia, Argentina and United States. Furthermore, federalism has developed and is still developing within each country in different ways, according to the government in power and historical events that contribute to the power in order to be exercised in a centralized or decentralized manner. In Brazil, there was more centralization in dictatorships terms, while more decentralization in democracy terms. Another essential matter in the formation of the differential trace of the several federalisms that came in the world, is how the Federation was formed in a historic perspective. Some federations are formed by aggregation, i.e., through union of sovereign and independent parties, that abdicate their sovereignty in exchange for certain autonomy in order to compose the federation. This is the natural formation of federations the word federation comes from the latin word foedus which means union. The United States of America, Canada and Australia were formed in such way. On the other hand, there are federations that were formed by segregation, i.e., from a Unitary State that empowers its administrative units hitherto exclusively dependent on central government. In this second group fits the Brazilian federalism model. All these differences and characteristics cause the federative entities from each federation to have more or less power and unit. A state of a federation formed by aggregation with a democratic political government will probably have powers greater than a state of a federation formed by segregation or living in a dictatorial government. In the first case, federalism by aggregation, the Union was created by the sovereign states that joined in a federation, while in the second, federalism by segregation, the central power was the one which created the states giving them some powers. Naturally, the first case will be more decentralized. However, the development of each federation can change the centralization of power, making a federation in origin centralized becomes more decentralized, as happened with Canada, while a federation decentralized in the origin ends up in a more centralized federation, as happened with the United States of America. In addition, the people from a state that has been sovereign before and gathered into Federation by a treaty, shall have greater interest in keeping the integrity of its territory than the people from a state that has never been sovereign and was created for the purpose of being part of the Federation. Similarly, in federations where each state represents an ethnic minority of the federation composed of several ethnicities, the states shall have greater unity. Thus, the people from ethnic states will have greater interest in the territorial integrity of the state. In the opposite sense, federations where territorial division does not separate people from distinct origins, nationalities and languages, but represents mere territorial boundaries of a homogeneous country, the bonds of unity in each state will be much weaker. Therefore, the territorial integrity of the states can be easily broken. In Brazil, there are only factors that weaken federative units: formation by segregation; the occurrence of authoritarian dictatorships that suppressed the autonomy of the states; and the absence of ethnic distinctions of Brazilians from a state to the other. Thus, the autonomy of the Brazilian states is weak, endangering even the territorial integrity of the states. Consequently, the states can easily have part of its territory dismembered to form new states or federal territories. Hence, since Independence of Brazil, there were several changes in the states territorial limits, forming new states. Moreover, there were a lot of proposals for new states creation by means of state limits alteration and redivision of the national territory. Such proposals have been formulated both in geographical studies of the Brazilian political and administrative organization, and projects examined by Congress or the Constitutional Conventions. The alterations in the territorial boundaries of states must obey the rule laid down in the Constitution. All Brazilian Constitutions have contemplated the possibility of alterations in the territorial limits of states. The Federal Constitution of 1988 was no different, setting forth in Article 18, paragraph 3, the alterations in the territorial boundaries that can be done (amalgamation, subdivision, dismemberment to be annexed to others states or to form new state or federal territory) and the procedure to be followed that involves: the approval of the population directly concerned, by means of a plebiscite; the audience of the Legislatures of the states concerned; and the Congress approval, through a supplemental law. The objective of this work is to study the adoption of the federalism in Brazil and the rest of the world and the rule that allows alterations in the territorial limits of states, checking the details of each constitutional requirement and the possibilities of effective application of this rule, which may cause the emergence of new states